The Survey of Independency Status Living in Elderly Referring to Tehran Civil Servants Pension Organization in 2015 - Akbarzadeh, Leila; Esmaeili, Roghayeh; Darvishpoor Kakhki, Ali; Nassiri, Malihe; Estebsari, Fatemeh (Advances in Nursing & Midwifery, 2018)
Abstract Introduction: elderly is one of the most sensitive ages in everyone’s life, thus regarding the everyday growth of the elderly population, caring for this vulnerable part of society is a necessity. Having in mind the confronting limitations in this era and lack of flexibility with environment, as well as decreasing independency status in the elderly, this study aims at evaluatin the amount of independent living in the elderly referring to Tehran Civil Servants Pension Organization (C.S.P.O) in 2015. Methods and Materials: This descriptive study was conducted on 260 elderly people referring to Tehran Civil Servants Pension Organization. Samples are selected via sapling method available in Civil Servants. The obtained data in this study were collected by standard questionnaire, including demographic characteristics and physical activity questionnaire in two sections, i.e. Activity Daily Living and Instrumental Activity Daily Living. After completing two questionnaires, the obtained data were analyzed using SPSS (ver. 23) through descriptive statistics, independent t-test, as well as One-way Anova. Results: The total mean score of age for the studied objects was 68.08 ± (7.63) years. The total mean score of independence in this group of elderly people has been independent (ADL= 13.61±1.14 & IADL= 14.77±3.79). Moreover, the total mean score of independence living in elderly with aging 60-74 years with incomes above 750 to 1 million dollars per month and the elderly with married, were higher. Discussion And Conclusion: elderly is a normal stage in the normal path of life for human beings, which is very different from other life stages. In general with increasing age decrease the level of independent living, and consequently the degree of dependence on others increases in the elderly. Also the elderly married who lives with wife and children and have better economic situation are more independent than the other. furthermore the obtained data in the current study and other studies reveals that the elderly people have the highest amount of independence in Activity Daily Living such as eating and sleeping, and Instrumental Activity Daily Living such as taking medicine and using telephone.